Malaysian Cinema, Asian Film Border Crossings and National Culture - van der Heide, William (Film Culture in Transition, 2002)
This monograph departs from traditional studies of national cinema by accentuating the intercultural and intertextual links between Malaysian films and Asian (as well as European and American) film practices. Using cross-cultural analysis, the author characterizes Malaysia as a pluralist society consisting of a multiplicity of cultural identities. Malaysian film reflects this remarkable heterogeneity, particularly evident in the impact of the Indian and Hong Kong cinema. Detailed analyses of a selection of Malaysian films highlight their cultural complexities, while noting the tension between cultural inclusivity and ethnic exclusivity at the heart of this cinema.